Committee on External Measurement and Reporting. (The Accounting Review, 1973)
The article presents a report of the Committee on External Measurement and Reporting of the American Accounting Association as of October 1973, which focused on the formulation of hypotheses in studying reporting problems. The Committee met several times to interpret and evaluate its charge and to select a limited number of propositions in areas where reporting problems are of immediate concern. The areas to be considered were identified in the reports cited in the charge and those of special interest to individual members of the Committee. A comparative evaluation of the importance of research projects in financial accounting would also have been helpful. The committee, because of various factors, was unable to respond fully to its charge, but perhaps the directions charted above will provide some stimulus to future researchers.